Constitutive modeling of amorphous thermoplastics from low to high strain rates: Formulation and critical comparison employing an optimization-based parameter identification. (15th June 2023) - Alves, A. Francisca Carvalho; Ferreira, Bernardo P.; Andrade Pires, F.M.
Abstract: A finite strain elasto-visco-plastic model is proposed to describe the low to high strain rate-dependent behavior of amorphous polymers. The predictive capability of the model is extensively assessed by comparing its numerical response against experimental data and some state-of-the-art models for both polycarbonate (PC) and poly(methyl methacrylate) (PMMA). A program is developed to expedite the implementation of different material models by accounting only for the model's constitutive equations instead of the numerical derivation of their state update procedure and consistent tangent operator. A two-stage optimization-based calibration procedure is proposed to determine the models' material parameters efficiently. The models are compared for the same set of experimental compression tests, and each model's material parameters are identified with the adaptive LIPO optimizer, providing a significant speed-up compared to the classical trial-and-error calibration approach. The experimental–numerical comparison shows that the proposed constitutive model is in close agreement with the experimental data for a wide range of strain rates, and slightly outperforms the state-of-the-art constitutive models in predicting the behavior of PC. All models present limitations in predicting the intricate behavior of PMMA, where the proposed constitutive model predicted excessive hardening at medium to high strain rates. Highlights: An elasto-visco-plastic model is proposed from low to high strain rates. A new unsupervised two-stage optimization-based calibration strategy is developed. Comparison of the predictions of different constitutive models for the same material. Close agreement with experimental and numerical results from the literature.